Hospitalisations, admission costs and re-fracture risk related to osteoporosis in Western Australia are substantial: A 10-year review - Briggs, Andrew; Sun, W.; Miller, L.; Geelhoed, E.; Huska, A.; Inderjeeth, C. (Wiley-Blackwell, 2015)
© 2015 Public Health Association of Australia. Objective: To quantify hospitalisation costs to Western Australia (WA) for osteoporosis-related fractures and estimate risk of readmission after incident fracture. Methods: All hospitalisation records for WA residents aged ≥ 50 years admitted to a WA hospital between 2002 and 2011 due to osteoporotic fractures were extracted from the WA Hospital Morbidity Data System. Data linkage enabled identification of the first (index) fracture admission, determination of subsequent osteoporotic fracture-related readmissions, and quantification of total admission costs and bed days. Cox proportional hazard models assessed factors influencing first readmission. Results: A total of 5,326 patients were admitted to WA hospitals for an index fracture. Of the 2,037 (38.2%) patients who sustained a re-fracture requiring readmission, 1,223 (23.0%) had one re-fracture episode, 453 (8.5%) has two, and 361 (6.8%) has three or more re-fracture episodes requiring readmission. Cost of index admissions was $57,007,262 while $48,948,623 was associated with readmissions (CPI-adjusted to 2011/12). Cumulative probability of readmission within six months of the index admission was 20% (males) and 17% (females). Conclusions: Osteoporotic fracture-related hospitalisations impose a substantial financial impact on WA, exceeding $100 million in a decade. Implications: Considering the large system costs, policy and programs to improve identification of index fractures and initiation of osteoporosis treatments and primary prevention initiatives are justified.